Detection of circulating tumor cells (CTCs) in cerebrospinal fluid of a patient with HER2-overexpressing gastric cancer and single cell analysis of intra-patient heterogeneity of CTCs - Cho, Jang Ho; Kim, Sun Young; Lee, Jeeyun; Park, Se Hoon; Park, Joon Oh; Park, Young Suk; Lim, Ho Yeong; Kang, Won Ki; Kim, Seung Tae (Translational Cancer Research, 2019)
Background: The purpose of this study was to identify circulating tumor cells (CTCs) through single cell sorting using DEPArray technology in cerebrospinal fluid (CSF) samples from an advanced gastric cancer (AGC) patient with leptomeningeal seeding. We also demonstrated intra-patient heterogeneity of CTCs isolated from CSF samples at the single cell level. Methods: We used the DEPArray system to identify and align single enabled CSF and CTCs based on a multi-parallel fluorescence analysis. The CSF samples were stained with an antibody cocktail recognizing DAPI, cytokeratin, EpCAM, and HER2. The stained cells were sorted and identified into a single, variable cell based on a multiparametric fluorescence analysis. The CSF and CTC subpopulations were quantified for absolute cell counts and relative frequency. Based on the stained morphology of each single CSF and CTC, five groups were identified. Results: We stratified the CTCs to evaluate the character of the CTCs isolated from the CSF, according to CK, EpCAM and HER2. In total, 78.2% of the CTCs isolated from the CSF showed HER2 overexpression, which was consistent with the status of HER2 in the patient’s primary gastric tumor. The most common types were HER2 positive, CK positive, and EpCAM positive CTCs (56.6%). On the other hand, 21.8% of the CTCs isolated from the CSF did not show HER2 overexpression, which was inconsistent with the primary tumor. Her2 negative, CK negative, and EpCAM positive CTCs were the predominant types among the CTCs without HER2 overexpression (19.7%). Conclusions: We enriched the CTCs through a single cell sorting process with DEPArray technology in CSF samples of an AGC patient with leptomeningeal seeding. We also demonstrated intra-patient heterogeneity of the CTCs at the single cell level.